Advanced Biopolymer-Based Soil Strengthening Binder with Trivalent Chromium-Xanthan Gum Crosslinking for Wet Strength and Durability Enhancement - Lee, Minhyeong; Chang, Ilhan; Cho, Gye Chun (Journal of Materials in Civil Engineering, 2023)
Xanthan gum (XG) is an effective soil-binding material for enhancing the geotechnical engineering performance of soil. Due to the hydrophilicity of XG, however, its ineffectiveness as a soil-strengthening agent in wet conditions and the associated durability concerns continue to be obstacles to the implementation of XG soil treatment. Here, we investigated the effect of trivalent chromium (Cr3+) crosslinking on the rheology of XG hydrogels, and consequent variations in the unconfined compressive strength of XG-Cr3+-treated soil. Rheological tests revealed that the crosslinking of Cr3+ initially increased the yield stress of the XG gel; as the gel cured, the XG-Cr3+ gel lost its viscoelasticity and became stiffer and more elastic. With increased Cr3+ and XG concentrations, the time-controllable gelation enhanced the unconfined compressive strength of the sandy soil in a hydrated state. Furthermore, the crosslinking of XG and Cr3+ reduced the swelling of the XG gel and increased strength durability of XG-Cr3+-treated soil under prolonged saturation conditions. Due to the fact that Cr3+ crosslinking effectively improved the wet strength and durability without additional dehydration or heat treatment, this method can expand the applicability of XG soil treatment, such as injection grouting or backfill material for various geotechnical engineering structures.
Keywords: Binding materials; Grouting materials; Soil strengthening; Soil treatments; Soils improvement; Treated soils; Trivalent chromium; Unconfined compressive strength; Wet strength; Xanthan gum; Crosslinking; Durability; Grouting material; Soil improvement; Trivalent chromium; Wet strength; Xanthan gum (XG)